Increased Long-Term Risks of Occupational Diseases in Homecare Nurses: A Nationwide Population-Based Retrospective Cohort Study - Hua-Yin Hsu; Chia-Chi Hsieh; Yi-Chen Tseng; Chiu-Hsia Hung; Kow-Tong Chen; Chun-Hsiang Wang; Yuan-Tsung Tseng (Mary Ann Liebert, 2020)
Background: The work of homecare nurses is different from that of general hospital nurses; therefore, it is necessary to understand the risks of occupational diseases in homecare nurses. Materials and Methods: In this retrospective cohort research conducted from 2000 to 2013, nursing staff comprised the sample obtained from the National Health Insurance Research Database. Nursing staff were subgrouped according to practice site into homecare, medical center, regional hospital, and local community hospital nurses. The control group included 4,108 subjects. Results: The risk of severe kidney disease was higher in homecare nurses than in medical center nurses (hazard ratio [HR]: 7.3, 95% confidence interval [CI]: 2.45?21.78) and regional hospital nurses (HR: 3.30, 95% CI: 1.37?7.96). The risk of severe liver disease was higher in homecare nurses than in medical center nurses (HR: 1.92, 95% CI: 1.10?3.35) and regional hospital nurses (HR: 2.06, 95% CI: 1.17?3.62). Conclusions: The prevalence of occupational diseases was higher in homecare nurses than in noncaregivers. The correlation between different practice environments and disease prevalence rates revealed that various types of nurses can be ranked in the following order based on the prevalence of the aforementioned diseases: homecare nurses > local community hospital nurses > regional hospital nurses > medical center nurses.